A global view of transcriptome dynamics during flower development in chickpea by deep sequencing. Issue 6 (1st April 2013) - Singh, Vikash K.; Garg, Rohini; Jain, Mukesh
Summary: Measurement of gene expression can provide important clues about gene function and molecular basis of developmental processes. Here, we have analysed the chickpea transcriptome in vegetative and flower tissues by exploiting the potential of high‐throughput sequencing to measure gene expression. We mapped more than 295 million reads to quantify the transcript abundance during flower development. We detected the expression of more than 90% genes in at least one tissue analysed. We found quite a large number of genes were differentially expressed during flower development as compared to vegetative tissues. Further, we identified several genes expressed in a stage‐specific manner. Various transcription factor families and metabolic pathways involved in flower development were elucidated. The members of MADS‐box family were most represented among the transcription factor genes up‐regulated during various stages of flower development. The abundant expression of several well‐known genes implicated in flower development in chickpea flower development stages confirmed our results. In addition, we detected the expression specificities of lineage‐specific genes during flower development. The expression data presented in this study is the most comprehensive dataset available for chickpea as of now and will serve as resource for unraveling the functions of many specific genes involved in flower development in chickpea and other legumes.